2001
DOI: 10.1128/aem.67.7.3058-3063.2001
|View full text |Cite
|
Sign up to set email alerts
|

Killer Toxin ofKluyveromyces phaffiiDBVPG 6076 as a Biopreservative Agent To Control Apiculate Wine Yeasts

Abstract: The use of Kluyveromyces phaffii DBVPG 6076 killer toxin against apiculate wine yeasts has been investigated. The killer toxin of K. phaffii DBVPG 6076 showed extensive anti-Hanseniaspora activity against strains isolated from grape samples. The proteinaceous killer toxin was found to be active in the pH range of 3 to 5 and at temperatures lower than 40°C. These biochemical properties would allow the use of K. phaffii killer toxin in wine making. Fungicidal or fungistatic effects depend on the toxin concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
79
0
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 30 publications
7
79
0
7
Order By: Relevance
“…Yeast strains often achieve competitive advantage by producing killer toxins, which kill off competing sensitive cells belonging to either the same or a different species (Young, 1987;Ciani & Fatichenti, 2001). The most thoroughly studied examples are the Saccharomyces cerevisiae toxins K1, K2 and K28; producers of these toxins are able to kill each other, but are immune to killer toxins of their own class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast strains often achieve competitive advantage by producing killer toxins, which kill off competing sensitive cells belonging to either the same or a different species (Young, 1987;Ciani & Fatichenti, 2001). The most thoroughly studied examples are the Saccharomyces cerevisiae toxins K1, K2 and K28; producers of these toxins are able to kill each other, but are immune to killer toxins of their own class.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, biocides have been used to deal with these problems but different disadvantages such as establishment of resistant strains and suppression of natural competitors have made alternatives such as biological control necessary (Beever et al, 1989;Raposo et al, 2000). Biological control strategies include natural plant-and animal-derived compounds, as well as antagonistic micro-organisms (Ciani & Fatichenti, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that Kluyveromyces phaffii (since reclassified as Tetrapisispora phaffii) (Ueda-Nishimura & Mikata, 1999) produces a killer toxin (KpKt) that is active on wine spoilage yeasts (Ciani & Fatichenti, 2001). KpKt has an extensive anti-Hansenispora/Kloeckera activity under winemaking conditions and, therefore, is of particular interest for its potential application as an antimicrobial agent in the wine industry (Ciani & Fatichenti, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…KpKt has an extensive anti-Hansenispora/Kloeckera activity under winemaking conditions and, therefore, is of particular interest for its potential application as an antimicrobial agent in the wine industry (Ciani & Fatichenti, 2001). At present, the inhibition of wild spoilage yeast at the prefermentative stage is achieved by the addition of SO 2 to freshly pressed must.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation